The risk-treatment paradox in non-ST-elevation myocardial infarction patients according to their estimated GRACE risk. (1st December 2018) - Saar, Aet; Marandi, Toomas; Ainla, Tiia; Fischer, Krista; Blöndal, Mai; Eha, Jaan
Abstract: Background: The purpose was to describe the treatment and outcomes of non-ST-elevation myocardial infarction (NSTEMI) in Estonia according to patients' estimated mortality risk by the Global Registry of Acute Coronary Events (GRACE) score and investigate if inequalities in treatment had an impact on prognosis. Methods: We performed a linkage between Estonian Myocardial Infarction Registry, Population Registry and Estonian Health Insurance Fund. All NSTEMI patients 2012–2014 were stratified into low (<4%), intermediate (4–12%), or high (>12%) mortality risk according to GRACE. All-cause mortality and composite endpoint of death, recurrent myocardial infarction, stroke or unplanned revascularization were compared between optimally – defined as concomitant in-hospital use of medicines from recommended groups and coronary angiography – and suboptimally managed patients, using the Cox regression. Results: Out of 3803 NSTEMI patients (median age 73 years, 44% women) 20% were classified into low, 35% into intermediate and 45% into high risk category. In these groups, respectively, 62%, 46% and 23% of patients received optimal in-hospital management. Over the mean follow-up of 2.4 years the association between suboptimal in-hospital management and outcomes was the following: in the low risk group mortality hazard ratio (HR) 1.6 (95% confidence interval 0.8–3.2), composite endpoint HR 1.2 (0.8–1.8); in the intermediate risk group mortality HR 2.4 (1.7–3.3), composite endpoint HR 1.8 (1.4–2.3); and in the high risk group mortality HR 2.2 (1.8–2.8), composite endpoint HR 1.6 (1.3–2.0). Conclusions: Higher risk NSTEMI patients received less guideline-recommended in-hospital management, which was associated with a worse prognosis. Highlights: Myocardial infarction patients' treatment depends on their estimated mortality risk. Intermediate and high risk patients undergo less often coronary angiography. Higher risk patients receive less in-hospital pharmacotherapy. Less intensive treatment seems to translate into higher mortality rates.